2019
DOI: 10.4143/crt.2017.468
|View full text |Cite
|
Sign up to set email alerts
|

Medical Travel among Non-Seoul Residents to Seek Prostate Cancer Treatment in Medical Facilities of Seoul

Abstract: The general trend of patients travelling from outside Seoul for prostate cancer treatment decreased from 2005 to 2014. However, a large proportion remained irrespective of direct distance from Seoul.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The current study followed a single-subject research design that is appropriate for small sample sizes and multiple repeated measures over a period of time ( Dattilo et al, 2000 ). In single-subject research, changes in a participant’s behavior are plotted on a graph and analysis is done visually without the use of inferential statistical analysis ( Kim and Kim, 2009 ). For this study, an A-B-A, labeled as “A1-B-A2,” single subject research design was used and administered in three phases: baseline (A1), intervention (B), and final baseline (A2).…”
Section: Methodsmentioning
confidence: 99%
“…The current study followed a single-subject research design that is appropriate for small sample sizes and multiple repeated measures over a period of time ( Dattilo et al, 2000 ). In single-subject research, changes in a participant’s behavior are plotted on a graph and analysis is done visually without the use of inferential statistical analysis ( Kim and Kim, 2009 ). For this study, an A-B-A, labeled as “A1-B-A2,” single subject research design was used and administered in three phases: baseline (A1), intervention (B), and final baseline (A2).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study reported that radiation therapy for Pca, including stereotactic body radiation, had continuously increased from 2005 to 2014. Considering these two factors, economic burden did not affect the choice of Pca treatment 35…”
Section: Discussionmentioning
confidence: 99%
“…Unless Pca detection rates decreased, this meant that Pca patients chose other treatment options, such as watchful waiting, active surveillance, radiation therapy, and hormone therapy. Because Pca incidence was not decreased and Pca mortality was slightly increased in South Korea, the stabilization or decrease in Pca prevalence could be explained by a decrease in the utilization rate of medical services 22,23…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 80% of PCa patients were over 65 years old in 2014. The incidence and prevalence of PCa have continuously increased [3,4].…”
Section: Introductionmentioning
confidence: 99%